\(\sqrt{\frac{a}{x}\sqrt{\frac{1}{ax}\frac{\sqrt{a}}{\sqrt{x^{3}}}}}\)ax1axax3the square root of a over x end-fraction the square root of 1 over a x end-fraction the fraction with numerator the square root of a end-root and denominator the square root of x cubed end-root end-fraction end-root end-rootπ‘Žπ‘₯1π‘Žπ‘₯π‘Žβˆšπ‘₯3√⎷⎷

1 answer

To simplify the expression

\[ \sqrt{\frac{a}{x}\sqrt{\frac{1}{ax}\frac{\sqrt{a}}{\sqrt{x^{3}}}}} \]

we'll break it down step by step.

  1. Inside the inner square root:

    Let's first simplify the expression inside the inner square root: \[ \frac{1}{ax} \cdot \frac{\sqrt{a}}{\sqrt{x^3}} = \frac{\sqrt{a}}{ax\sqrt{x^3}} = \frac{\sqrt{a}}{a\sqrt{x}\cdot x^{3/2}} = \frac{\sqrt{a}}{a x^{2}} = \frac{1}{\sqrt{a}} \cdot \frac{1}{x^{2}} \]

    So the inner square root simplifies to: \[ \sqrt{\frac{1}{ax}\cdot \frac{\sqrt{a}}{\sqrt{x^3}}} = \sqrt{\frac{1}{a x^2}} \]

  2. Now substitute back:

    Substitute back into the outer square root: \[ \sqrt{\frac{a}{x} \cdot \sqrt{\frac{1}{a x^2}}} \]

    This becomes: \[ \sqrt{\frac{a}{x} \cdot \frac{1}{\sqrt{a x^2}}} = \sqrt{\frac{a}{x} \cdot \frac{1}{\sqrt{a} \sqrt{x^2}}} = \sqrt{\frac{a}{x} \cdot \frac{1}{\sqrt{a}x}} = \sqrt{\frac{1}{\sqrt{a}} \cdot \frac{1}{x^2}} \]

  3. Combine fractions:

    Combine the components: \[ \sqrt{\frac{1}{\sqrt{a} \cdot x^2}} = \frac{1}{\sqrt{\sqrt{a} \cdot x^2}} = \frac{1}{\sqrt{a^{1/2} x^2}} = \frac{1}{\sqrt{a^{1/2}} \cdot \sqrt{x^2}} = \frac{1}{\sqrt{a^{1/2}} \cdot x} = \frac{1}{\sqrt{a} x} \]

So the final simplified form of the original expression is

\[ \frac{1}{\sqrt{a} x} \]